Influencia de los canales alternativos en la satisfacción de los clientes del Centro de Contacto del Banco de Crédito del Perú - Sede Trujillo, 2015 - Aredo Rodriguez, Uber Jhony (2016)
This paper aims to determine the degree of customer satisfaction of Banco de Credito of Peru based contact center Trujillo. Bank credit is focused on providing the highest customer satisfaction not only providing excellent quality of service but also offering products and services that meet the expectations of its customers in general, to achieve customer satisfaction it has several alternative channels attention to offer their products and services and allow customers to carry out their various operations quickly and timely. Alternative channels are available to customers in general accounts who with various alternatives for conducting financial transactions and non-financial allowing them to save time, money and in many cases perform operations from the comfort of your home with just using technology . Scientific methods used in the research were the inductive method and the annalistic method, data collection instruments and survey and interview were also used to determine the degree of customer satisfaction by using alternative channels of BCP. The investigation resulted that customers are satisfied with the alternative channels offered by the BCP but need more information about the operations that can be performed and the conditions of use of alternative channels of BCP.